FAKTOR-FAKTOR YANG MEMPENGARUHI IBU TIDAK MENGGUNAKAN KONTRASEPSI IMPLANT DI KELURAHAN REJASARI KECAMATAN PURWOKERTO BARAT KABUPATEN BANYUMAS TAHUN 2015 - Nur Baety; Maya Safitri; Arni Nur Rahmawati (Universitas Harapan Bangsa Purwokerto, 2015)
Background: The use of birth control implant Achievement at the national, provincial, district and sub-district, the achievement is still low birth control implant. Acquisition ofnew family planning participants in Central Java as many as 997 425 acceptors with asmany as 89 436 implant acceptors (8.97%). This is due to lack of knowledge aboutcontraceptive implant, low education levels and socioeconomic levels were also lower.Based on the preliminary survey conducted in the Village Rejasari EFA number 572people, who use KB 375 KB acceptors and Implant only 11 acceptors.Objective: To determine the description of the factors that affect the mother does not usecontraceptive implants in Sub Rejasari District of West Purwokerto, Banyumas regency in2015.Methods: This research method is descriptive based on primary data taken using aquestionnaire. The population of all active family planning acceptors in addition toimplant in the Village Rejasari District of West Purwokerto, Banyumas regency totaling364 acceptors. The sample used to use formulas slovin sampel.Pengambilan obtained 78samples was done by using purposive sampling.Analisis data used univariate analysisResults: Most respondents have less knowledge about contraceptive implant that is asmuch as 32 respondents (41%), primary education is 48 respondents (61.5%) andeconomic level were as many as 34 respondents (43.6%).Conclusions: description of the factors that affect the mother does not use contraceptiveimplants in Sub Rejasari District of West Purwokerto, Banyumas regency in 2015 amongwhich the lack of knowledge, basic education and economic levels being. Keywords: Knowledge, education, socio-economic, contraceptive implant